ANALISIS KINERJA KEUANGAN BERDASARKAN PENDEKATAN ECONOMIC VALUE ADDED (EVA) (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2012)
The concept of financial performance that are beginning to be explored is the Economic Value Added (EVA) and Market Value Added (MVA). Economic Value Added (EVA) measure company performance in the current period while the Market Value Added (MVA) assessment reflects the market on the company's prospects in the future. This study aimed to: 1) Know the EVA approach to assess the performance of the company 2) To know the influence of EVA on stock returns. In this study, the population criterion is Company entered LQ 45 during the period 2004-2008. Samples were obtained through purposive sampling technique to obtain the 10 companies sampled. Data analysis techniques used in this research is descriptive and quantitative analysis The results of this study show that: 1) Economic Value Added (EVA) sample firms during the observation period is negative 2) EVA significant effect on stock returns.